Complexity and context : staff support systems in mental health after critical incidents and traumatic events : a thesis presented in partial fulfilment of the requirement for the degree of Doctor of Philosophy in Social Work, School of Sociology, Social Policy and Social Work, Massey University, Wellington, New Zealand - Adamson, Carole (Massey University, 2005)
This thesis presents an ecological exploration of the experiences of mental health workers faced with critical incidents and traumatic events in the course of their work. A qualitative study, it takes the experiences of twenty workers from a range of disciplines and environments, and examines their preparation for exposure to extreme stress, their passage through the incidents that they chose to relate, and the organisational response to the events. The central research question explores the knowledge bases currently utilised within trauma and critical incident response, and the degree to which these provide adequate explanatory, practice and evaluation models for responses to workplace incidents. It is examined through the narratives of the mental health workers, who self-define and explore the nature of their preparation for, and experience of, critical incidents and traumatic events in their workplace. The question is contextualised through a review of the knowledge bases of trauma and extreme stress, and of the mental health environment in which the workers practice. A case study of the workplace support known as debriefing illustrates the tensions between current knowledge bases in the area. Informed by this, the key issues of what did or did not work for the participants are explored. The thesis argues that the paradigm shift signalled by the latest developments within conceptualisations of trauma is not yet complete, and that the ensuing tensions have created debate and confusion in the creation of adequate responses to workplace incidents. Whilst conceptualisations that attempt to address issues of complexity and context are evolving, it is argued that an ecological framework has the potential to both explain and respond to incidents that occur within the mental health environment. The findings of the research raise issues of complexity in the design and implementation of appropriate support systems, and lend a perspective to the critique of debriefing that has been missing from existing debates. Key principles for the development of safe and sound support systems, and their evaluation, are developed.
Keywords: Extreme stress; Organisational response; Workplace incidents; Fields of Research::370000 Studies in Human Society::370200 Social Work::370204 Counselling , welfare and community services